Climatic niche comparison of raccoons Procyon lotor and raccoon dogs Nyctereutes procyonoides in their native and non‐native ranges. (7th April 2021) - Kochmann, Judith; Cunze, Sarah; Klimpel, Sven
Abstract: During the last century, the practice of fur farming in Europe led to the introduction of two mammal species from opposite ends of the world. With their subsequent unintentional escape from captivity or intentional releases, the process of slow expansion and establishment in Europe began. The raccoon Procyon lotor and the raccoon dog Nyctereutes procyonoides are included on the European Union's list of invasive alien species. We characterised the current climatic niches of the two species in their native ranges in North America and Asia, and compared them with their non‐native‐range niches in Europe, where we also projected climatic suitability. The aim was to locate suitable habitats beyond their current ranges and assess where a range expansion can be expected. Niche comparison and the projection of climatic suitability in Europe were based on eight bioclimatic variables and presence records from the Global Biodiversity Information Facility database. For niche modelling, we applied the maximum entropy approach (Maxent) and used the native‐range data for training. Minimum temperature of the coldest month (bio06) was identified as the most important bioclimatic variable in the habitat suitability models for both species. Different tolerance levels regarding this variable might explain small differences between the species' projected ranges, especially in the north and east of Europe. The high niche unfilling for both species in Europe suggests a potential for expansion beyond their present ranges. With only little understanding of their ecological impacts in their new ranges, including the potential risk of Nyctereutes procyonoides as SARS‐CoV‐2 reservoir hosts, further research and management is required at various spatial scales in Europe. Abstract : During the last century, the practice of fur farming in Europe led to the introduction of the raccoon Procyon lotor and the raccoon dog Nyctereutes procyonoides . Procyon lotor originates from the North American continent, whereas the original distribution of Nyctereutes procyonoides lies in eastern Asia. Both species managed to escape from captivity and are now included on the European Union's list of invasive alien species. We compared the climatic niches of both species in their native ranges with their non‐native‐range niches based on eight bioclimatic variables and presence records from the Global Biodiversity Information Facility database. The high niche unfilling for both species in Europe suggests a potential for expansion beyond their present ranges. We also projected climatic suitability in Europe to locate suitable habitats beyond their current ranges. With only little understanding of their ecological impacts in their new ranges, including the potential risk of Nyctereutes procyonoides as SARS‐CoV‐2 reservoir hosts, further research and management is required at various spatial scales in Europe.